Challenges due to the reliance on manual processes and human error: the use of technology in companies - Nasrudin, Nurin Izzdhinie; Mohamad, Amri (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
When the processes to produce the financial reports are done manually by humans fully, it leads to human error in accounting. There are a lot of difficulties, burdens and losses that are caused by human error in accounting. The process is long and a bit complicated that requires humans to do it manually. Therefore, it increases the chance of human error or fraud. It also leads to taking extra time and energy to do checking and correcting. Living in this globalized era, there are things that have changed to suit the modernization and human’s need. In this new era of technology, all industries are supposed to take advantage of the technology. Data automation, blockchain, cloud computing and artificial intelligence (AI) are the several technologies that are the latest and advanced that could improve the living and reduce the work burden.